Theme-Rheme and Thematic Progression in Obama’s Speech and Its Translation - Mufti Rizki Oktaviani (Universitas Pendidikan Indonesia (UPI), 2013)
The study entitled Theme-Rheme and Thematic Progression in Obama’s Speech and Its Translation focuses on how a translator puts differences in worldview between the source and the target language text. The differences of worldview itself can be found by analyzing each sentence chosen by the translator. This study used Theme-Rheme and Thematic Progression as proposed by Halliday, which is developed by Gerot and Wignell (1994) and Eggins (2004). The study shows that both texts use Participants as the most frequently used theme. However, the text in the target language considers Participants much more important than the text in source language does. Meanwhile, the analysis of thematic progression shows that both texts use Theme Reiteration. It can be concluded that both texts tend to be monotonous because Obama often begins the speech with the same words.Keywords: Theme-Rheme, Thematic Progression, Worldview, Speech.